Impact of SARS-CoV-2-specific memory B cells on the immune response after mRNA-based Comirnaty vaccine in seronegative health care workers - Vallejo, Alejandro; Vizcarra, Pilar; Martín-Hondarza, Adrián; Gómez-Maldonado, Sandra; Haemmerle, Johannes; Velasco, Héctor; Casado, José L. (Frontiers in Microbiology, 2022)
Purpose: To analyze the impact of SARS-COV-2-specific memory B cells (MBC) on the immune response after two doses of mRNA-based Comirnaty COVID-19 vaccine in seronegative health care workers. This study is seeking a rationale for boosting vaccines. Methods: Longitudinal study including 31 seronegative health care workers with undetectable MBCs (IgG-MBC- group), 24 seronegative with detectable MBCs (IgG-MBC+ group), and 24 seropositive with detectable MBCs (IgG+MBC+ group). The level of neutralizing, anti-S IgG, IgA, and IgM antibodies were quantified by ELISA. In addition, specific memory B and T cells were quantified by flow cytometry. Results: The level of specific MBCs, and isotypes, in the IgG-MBC- group was lower compared to that found in IgG-MBC+ (p=0.0001) and IgG+MBC+ (p<0.0001) groups, respectively. Neutralizing and anti-S IgG antibodies were at lower levels in the IgG-MBC- group after the vaccine. Specific MBCs directly correlated with specific CD4+ T cells (although not significant, p=0.065), while no correlation was found with specific CD8+ T cells (p=0.156) after the vaccine. In parallel, neutralizing antibodies only positively correlated with specific CD4+ T cells (p=0.034). Conclusions: IgG-MBC- individuals showed the worst humoral and cellular responses, both in frequency and magnitude, after vaccine. Individuals whose antibodies wane and become undetectable after a given period of time post vaccine and show no specific MBCs are less protected and hence are good candidates for boosting vaccine. On the other hand, seronegative individuals with specific MBC showed faster and higher responses compared to the IgG-MBC- group.